FEATURES OF CONDUCTING MUSIC LESSONS REMOTELY IN PRIMARY SCHOOL - Ashykhmina , Nataliia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article examines the specifics of conducting distance music lessons in primary school under martial law and amid the global transformation of the educational process. It highlights the challenges associated with emotional interaction, collective creativity, and the age-related characteristics of young learners. It is noted that the effectiveness of distance learning largely depends on the application of interactive, student-centered, and game-based strategies, as well as the use of multimedia platforms and mobile applications. The article analyzes the experience of international schools and scientific approaches to the organization of blended learning. The importance of developing digital competence among music teachers, involving parents in creating a comfortable learning environment, and implementing musically and culturally relevant content is emphasized. Particular attention is given to the promising potential of combining synchronous and asynchronous platforms to facilitate creative musical tasks and maintain emotional connection with students. The article concludes that the digital transformation strategy for conducting music lessons in primary school should be based on a combination of pedagogical flexibility, technological innovation, and psychological and age appropriateness.